Study on arsenic removal process from water - Bayarmaa, B; Selenge, E; Min, Yang (Mongolian Journal of Chemistry, 2014)
In this study a novel adsorbent, iron oxide, is used for As (V) or As (III) removal. Some ferric oxides have been reported to be effective for arsenic removal. Ferric oxides powder is a good adsorbent material since it’s has magnetic properties and a good adsorption capacity. The main purpose of this study has been focused on to study the relationship between adsorption capacity (ability, performance) and the surface characteristics of the ferric oxide. Prepared sample’s capacity was evaluated. The value was 26.1-67.4 mg/g for As (V) and 20.5-47.8 mg/g for As (III). pH dependence was evaluated and when pH increasing, adsorption capacity was decreased. The kinetic was evaluated and about 12 hours reached equilibrium and a capacity of 49 mg/g for As (V) and 42 mg/g for As(III) was gained. The kinetic constants for arsenic adsorption on the ferrihydrite adsorbent’s were fitted. DOI: http://dx.doi.org/10.5564/mjc.v12i0.172 Mongolian Journal of Chemistry Vol.12 2011: 53-55